Paul's theology of preaching : the apostle's challenge to the art of persuasion in ancient Corinth - Litfin, A. Duane (InterVarsity Press, 2015)
This revised and expanded version of Litfin's previous St. Paul's Theology of Proclamation will provide insight to those engaged in Pauline and New Testament studies, rhetorical theory and Greco-Roman studies. Moreover, by offering a better understanding of Paul's method as well as the content of his declaration concerning 'the power and wisdom of God' revealed in Jesus, this book will help preachers as they 'preach Christ crucified.'